Consumptive Behavior of Students in Shopping Online and Implications in Guidance and Counseling Services in Universities - Nelvi Mitra; Syahniar Syahniar; Alizamar Alizamar (International Journal of Research in Counseling and Education, 2019)
The purpose of this study wasto examine consumer consumption behavior in shopping online. It also aimed to establishthe factors promoting students desires to transact online. Importantly, the study used qualitative research methods. The results showed that consumption behaviorswere not based on needs but rather the desires, they are easily influenced by friends and follow the latest trends, discounts, or promos in the online shop. There are other additional factors with significant influence of consumption patterns. These include price, convenience, trust, availability of goods, and the promotions attractingtheirattention. Therefore, counselors should utilize information services, group guidance, and individual counseling services to regulate students behavior.